The Effect of Leverage and Liquidity on Company Value with Profitability as a Mediation Variable - SS, Muh Fathul Mubaraq; Musyaffi, Ayatulloh Michael; Buchdadi, Agung Dharmawan (Indonesian Journal of Advanced Research, 2025)
This research explores how leverage and liquidity influence firm value, with profitability acting as a mediating factor. A quantitative method was utilized, employing SPSS version 30 along with Multiple Linear Regression and the Sobel Test for data analysis. The study focused on companies within the technology sector listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. A total of 13 companies were selected as samples, resulting in 52 data points. The findings show that leverage has no significant effect on firm value. Liquidity has no significant effect on firm value. Leverage has a positive and significant effect on profitability. Liquidity has a positive and significant effect on profitability. Profitability has a positive and significant effect on firm value. Leverage has a positive and significant effect on firm value through profitability. Liquidity does not have a significant effect on firm value through profitability.